The elements of investing easy lessons for every investor - Malkiel, Burton Gordon (John Wiley & Sons, Inc., 2013)
BAn updated look at best rules of investing provided by two of the world's greatest financial thinkers/b In the updated edition of iThe Elements of Investing, /i authors Charles Ellis and Burton Malkiel'two of the world's greatest financial thinkers'have again combined their talents to produce a straight-talking book about investing and saving. Written with every investor in mind, this reliable resource will put you on a path towards a lifetime of financial success. Page by page, Malkiel and Ellis skillfully focus their message to address the essentials and offer a set of simple, but powerful thoughts on how to avoid Mr. Market and his "loser's game," and instead enjoy the "winner's" approach to investing. All the investment rules and principles you need to succeed are here'with clear advice on how to follow them.ulliShows you how to focus on the long term instead of following market fluctuations that are likely to lead to costly investing mistakes/liliContains investment insights that can carry you all the way to, and through, retirement/liliWritten by Burton G. Malkiel, the bestselling author of iA Random Walk Down Wall Street, /i and Charles D. Ellis, the bestselling author of iWinning the Loser's Game/i/ul A disciplined approach to investing, complemented by understanding, is all you need to enjoy success. This practical guide explains what you really need to know and puts you on the right course for long-term success through all kinds of markets.
Includes index. - Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Investments; Finance, Personal; Portfolio management; Investment analysis; Business enterprises -- Finance; Corporations -- Finance; Investissements; Gestion de portefeuille; Analyse financière; portfolios (financial records); BUSINESS & ECONOMICS; Investments & Securities; General; Corporations; Finance; Business enterprises; Finance